Pressure-sensitive adhesive layer, pressure-sensitive adhesive film, and optical film with pressure-sensitive adhesive layer

The adhesive layer, composed of an acrylic polymer copolymerized with butyl (meth)acrylate and a hydroxyl group-containing monomer, addresses the need for low dielectric constant and loss, flexibility, and durability in bonding optical members in liquid crystal panels, enhancing visibility and reducing noise interference.

JP7665718B2Active Publication Date: 2025-04-21ZACROS CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2023201791
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-11-29
Publication Date
2025-04-21
Estimated Expiration
2034-12-09

AI Technical Summary

Technical Problem

Existing adhesive layers and films used for bonding optical members in liquid crystal panels lack a combination of low dielectric constant, low dielectric loss, flexibility, rigidity, durability, and reworkability.

Method used

A pressure-sensitive adhesive layer composed of an acrylic polymer copolymerized with butyl (meth)acrylate, a hydroxyl group-containing monomer, and a crosslinking agent such as tolylene diisocyanate, along with a silane coupling agent, to achieve a lower dielectric constant and dielectric loss while maintaining flexibility and durability.

Benefits of technology

The adhesive layer achieves a lower dielectric constant and dielectric loss, combining flexibility, rigidity, durability, and reworkability, making it suitable for bonding optical members in liquid crystal panels, particularly in on-cell panels, to enhance visibility and reduce noise interference.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007665718000005
    Figure 0007665718000005
  • Figure 0007665718000006
    Figure 0007665718000006
  • Figure 0007665718000001
    Figure 0007665718000001
Patent Text Reader

Abstract

To provide an adhesive layer having lower values of a dielectric constant and a dielectric loss compared to conventional adhesive layers, and having all of flexibility, rigidity, durability and reworkability; an adhesive film; and an optical film with an adhesive layer.SOLUTION: An acrylic polymer is obtained by copolymerizing a total of 100 pts.wt. of (A) a monomer group consisting of an alkyl (meth)acrylate monomer, an alicyclic-containing monomer and a branched-structure alkyl group-containing monomer, and 0.1 to 0.5 pts.wt. of (B) a hydroxy group-containing copolymerizable vinyl monomer. The acrylic polymer contains butyl (meth)acrylate in a ratio of 30 pts.wt. or more and does not contain (meth)acrylate monomers with aromatic groups and carboxyl group-containing copolymerizable vinyl monomers. The acrylic polymer has an acid value of 0.1 or less and contains in a ratio of 0.01 to 1.5 pts.wt. of only the adduct of tolylene diisocyanate as a cross-linking agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive layer and an adhesive film used for bonding optical components such as polarizing plates. More specifically, the present invention provides an adhesive layer and an adhesive film that have low dielectric constant and dielectric loss values ​​and that are used for bonding optical components in the manufacture of liquid crystal panels with ITO films called on-cell panels, and that combine flexibility, rigidity, durability, and reworkability. [Background technology]

[0002] In recent years, various display devices, such as smartphones, tablet terminals, and tablet PCs, that have a capacitive touch panel attached to an external liquid crystal panel have been widely used. In such display devices, a physical space exists between the liquid crystal panel and the touch panel. This causes a problem that external light is reflected on the upper surface of the liquid crystal panel and the lower surface of the touch panel, reducing visibility, especially in bright environments such as outdoors.

[0003] As a method for solving the problem of reduced visibility, an in-cell type display device that incorporates touch panel functions into the pixels of the liquid crystal display has been proposed (see, for example, Patent Document 1). However, this has not been put to practical use due to the complex manufacturing process, which reduces product yields, and the technical difficulties of improving image display performance.

[0004] Meanwhile, on-cell type display devices have been proposed recently (see, for example, Patent Document 2). In on-cell type display devices, a touch sensor made of a transparent electrode pattern is formed between a color filter and a polarizing plate, and the function of a touch panel is built in between the color filter substrate and the polarizing plate. The on-cell type has the advantage of less reduction in product yield. For this reason, the on-cell type is expected to develop further as a promising manufacturing technology for liquid crystal panels incorporating touch panels.

[0005] However, since capacitive touch panels are sensors that detect changes in electromagnetic fields, they are susceptible to noise. To prevent erroneous recognition of the touch position, it has been proposed to laminate a low dielectric constant film in the laminate structure or to provide a low dielectric constant material in the wiring line of the capacitive sensor (see, for example, Patent Documents 3 to 5). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2009-258182 A [Patent Document 2] JP 2014-044501 A [Patent Document 3] JP 2013-082880 A [Patent Document 4] JP 2012-094017 A [Patent Document 5] JP 2013-003758 A Summary of the Invention [Problem to be solved by the invention]

[0007] Incidentally, the adhesive of Patent Document 3 has excellent insulating properties with a relative dielectric constant of 3.5 or less, but it is unclear whether the adhesive layer has flexibility and rigidity. Furthermore, Patent Documents 4 and 5 describe stacking a low dielectric constant film in the laminate structure of a capacitive touch panel to prevent erroneous recognition, and providing a low dielectric constant material in the wiring line of the capacitive sensor, but do not specifically disclose a manufacturing method for the low dielectric constant material used.

[0008] Thus, in the prior art, no adhesive layer or adhesive film was known that could be used for bonding optical components and that combined excellent insulating performance due to its low dielectric constant with flexibility, rigidity, durability, and reworkability. There is a need for a pressure-sensitive adhesive layer and a pressure-sensitive adhesive film that can be used to attach optical members and overcomes these requirements and problems in the prior art.

[0009] The present invention aims to provide an adhesive layer and an adhesive film which have a lower dielectric constant and dielectric loss value compared to conventional adhesive layers, and which combine flexibility, rigidity, durability and reworkability. [Means for solving the problem]

[0010] In order to solve the above problems, the pressure-sensitive adhesive layer of the present invention has the technical concept of using butyl (meth)acrylate as an essential monomer for the acrylic polymer, not using aromatic-containing monomers, not using carboxyl group-containing monomers as functional group-containing monomers but only hydroxyl group-containing monomers, using only an adduct of tolylene diisocyanate as a crosslinking agent for the copolymer, and further using a silane coupling agent in combination.

[0011] In order to solve the above-mentioned problems, the present invention provides a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer, a crosslinking agent, and a silane coupling agent, the acrylic polymer being a copolymer obtained by copolymerizing a total of 100 parts by weight of at least one monomer selected from a monomer group consisting of (A) an alkyl(meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer, and (B) 0.1 to 0.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer, the total of 100 parts by weight of (A) containing 30 to 100 parts by weight of butyl(meth)acrylate, the acid value of the acrylic polymer is 0.1 or less, and the crosslinking agent contains, relative to a total of 100 parts by weight of (A), 0.01 to 1.5 parts by weight of an isocyanate compound which is an adduct of tolylene diisocyanate alone, and 0.01 to 2.0 parts by weight of the silane coupling agent; the pressure-sensitive adhesive layer has a gel fraction of 40 to 75% after aging for 7 days under an atmosphere of 23°C and 50% RH; and the pressure-sensitive adhesive layer has a relative dielectric constant of 1.50 to 5.50 and a dielectric loss of 0.01 to 0.09 at a frequency of 100 kHz, as measured when laminated to a thickness of 1000 μm.

[0012] It is preferable that the acrylic polymer does not contain a (meth)acrylate monomer having an aromatic group and a carboxyl group-containing copolymerizable vinyl monomer, the acid value of the acrylic polymer is 0.1 or less, the crosslinking agent contains an isocyanate compound in an amount of 0.01 to 1.5 parts by weight per 100 parts by weight of the total of monomers excluding the hydroxyl group-containing copolymerizable vinyl monomer, the weight average molecular weight of the pressure-sensitive adhesive layer after crosslinking of the pressure-sensitive adhesive composition is 300,000 to 2,000,000, and the pressure-sensitive adhesive layer is laminated on one side of a substrate to a thickness of 25 μm and then has an adhesive strength of 1.5 to 10 N / 25 mm after lapse of 10 days at 23° C.

[0013] The pressure-sensitive adhesive composition preferably further contains 0.01 to 2.0 parts by weight of a silane coupling agent relative to 100 parts by weight of the total of monomers excluding the hydroxyl group-containing copolymerizable vinyl monomer.

[0014] The crosslinking agent is an isocyanate compound, and is preferably an adduct of tolylene diisocyanate with trimethylolpropane.

[0015] The hydroxyl group-containing copolymerizable vinyl monomer is preferably at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, and 2-hydroxyethyl (meth)acrylate.

[0016] The present invention also provides a pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer laminated on one surface of a substrate.

[0017] The pressure-sensitive adhesive film is preferably used for bonding a polarizing plate to a liquid crystal panel or an organic EL panel.

[0018] The present invention also provides an adhesive film, characterized in that the adhesive layer is formed on one side of a release film to a thickness of 1 μm to 25 μm, and has a structure of release film / adhesive layer / release film.

[0019] The present invention also provides an optical film with a pressure-sensitive adhesive layer, comprising an optical film and the pressure-sensitive adhesive layer laminated on at least one surface of the optical film.

[0020] The present invention also provides a polarizing plate with a pressure-sensitive adhesive layer, characterized in that the pressure-sensitive adhesive layer is laminated on one surface of a polarizing plate.

[0021] In the above-mentioned pressure-sensitive adhesive layer-attached polarizing plate, the pressure-sensitive adhesive layer is preferably used for bonding the polarizing plate to a retardation film having a retardation of λ / 4 or λ / 2.

[0022] The present invention also provides a liquid crystal panel comprising the above-mentioned pressure-sensitive adhesive layer-attached polarizing plate.

[0023] The present invention also provides an on-cell panel, comprising the above-mentioned pressure-sensitive adhesive layer-attached polarizing plate. Effect of the Invention

[0024] According to the present invention, an adhesive layer having a lower dielectric constant and dielectric loss value compared to conventional adhesive layers can be provided, and an adhesive layer and adhesive film that combine flexibility, rigidity, durability and reworkability can be provided. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 is a structural schematic diagram showing an example of a liquid crystal panel equipped with a conventional touch panel. [Diagram 2] FIG. 1 is a structural schematic diagram showing an example of a liquid crystal panel equipped with an on-cell type touch panel. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] Hereinafter, the present invention will be described based on preferred embodiments.

[0027] The present invention provides an adhesive layer and an adhesive film that combine flexibility, rigidity, durability and reworkability, and that are used for bonding optical components in the manufacture of liquid crystal panels with an ITO film known as on-cell panels.

[0028] 1 is a structural schematic diagram showing an example of a liquid crystal panel 5 equipped with a conventional touch panel. In such a display device using a liquid crystal panel equipped with a conventional touch panel, a physical space 4 exists between the liquid crystal panel 2 and the touch panel 1. This causes external light to be reflected on the upper surface of the liquid crystal panel 2 and the lower surface of the touch panel 1, resulting in a problem of reduced visibility, particularly in bright environments such as outdoors.

[0029] 2 is a structural schematic diagram showing an example of a liquid crystal panel 40 equipped with an on-cell type touch panel. In an on-cell type display device, a touch sensor 10 made of a transparent electrode pattern is formed between a color filter 13 and a polarizing plate 14, and the touch panel function is provided between the color filter 13 and the polarizing plate 14. The on-cell type has the advantage of less reduction in product yield. For this reason, the on-cell type is expected to develop further as a promising manufacturing technology for liquid crystal panels incorporating touch panels.

[0030] In FIG. 2, the adhesive layer used for bonding the optical component of the present invention has a lower dielectric constant and dielectric loss value than conventional adhesive layers, and therefore can be used for bonding the optical component between the polarizing plate 14 and the backlight unit 30 to reduce the effect of noise on a capacitive touch panel. The adhesive layer according to the present invention is particularly suitable for use in bonding two upper and lower polarizing plates 14 and 15 to a liquid crystal panel 20. Specifically, the adhesive layer according to the present invention is particularly suitable for use in bonding the polarizing plate 14 to a glass substrate 11 (also called ITO glass) having a touch sensor 10 attached thereto, and for bonding the polarizing plate 15 to a glass substrate 12 (also called TFT glass) having a TFT electrode 17 attached thereto.

[0031] The pressure-sensitive adhesive layer of the present invention is an adhesive layer obtained by crosslinking an adhesive composition containing an acrylic polymer and a crosslinking agent, the acrylic polymer being a copolymer obtained by copolymerizing at least one monomer selected from the group consisting of an alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer, and a hydroxyl group-containing copolymerizable vinyl monomer, the acrylic polymer containing 30 to 100 parts by weight of butyl (meth)acrylate and 0.1 to 3.5 parts by weight of the hydroxyl group-containing copolymerizable vinyl monomer relative to 100 parts by weight of the total of monomers excluding the hydroxyl group-containing copolymerizable vinyl monomer, the pressure-sensitive adhesive layer having a gel fraction of 40 to 75%, and the pressure-sensitive adhesive layer having a relative dielectric constant of 1.50 to 5.50 at a frequency of 100 kHz and a dielectric loss of 0.01 to 0.09, as measured when laminated to a thickness of 1000 μm.

[0032] The acrylic polymer according to the present invention is a copolymer obtained by copolymerizing at least one monomer belonging to the first monomer group and at least one monomer belonging to the second monomer group, the monomers being at least one selected from a group consisting of an alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer, as a monomer belonging to the first monomer group, and at least one hydroxyl group-containing copolymerizable vinyl monomer as a monomer belonging to the second monomer group. In this specification, (meth)acrylate is a general term for acrylate and methacrylate.

[0033] In the adhesive composition according to the present invention, the alkyl (meth)acrylate monomer having an alkyl group with carbon number of C1 to C14 may include at least one of methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, and tetradecyl (meth)acrylate. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic, but the alkyl group here is linear. The (meth)acrylate monomer having a branched alkyl group belongs to the branched structure alkyl group-containing monomer. Moreover, (meth)acrylate monomers having a cyclic alkyl group belong to the category of alicyclic-containing monomers. The acrylic polymer according to the present invention has butyl (meth)acrylate as an essential monomer. It is preferable that the acrylic polymer contains 30 to 100 parts by weight of butyl (meth)acrylate per 100 parts by weight of the total of monomers (monomers belonging to the first monomer group) excluding the hydroxyl group-containing copolymerizable vinyl monomer.

[0034] In the pressure-sensitive adhesive composition according to the present invention, the alicyclic-containing monomer may be at least one of cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, bicycloheptyl (meth)acrylate, bicyclooctyl (meth)acrylate, dimethylbicycloheptyl (meth)acrylate, dicyclopentanyl (meth)acrylate, etc. The alicyclic-containing monomer may be an alicyclic alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C18.

[0035] In the pressure-sensitive adhesive composition according to the present invention, examples of the branched alkyl group-containing monomer include at least one of isopropyl (meth)acrylate, isobutyl (meth)acrylate, t-butyl (meth)acrylate, isopentyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isononyl (meth)acrylate, isodecyl (meth)acrylate, isoundecyl (meth)acrylate, isododecyl (meth)acrylate, isotridecyl (meth)acrylate, isotetradecyl (meth)acrylate, isopentadecyl (meth)acrylate, isohexadecyl (meth)acrylate, isoheptadecyl (meth)acrylate, isooctadecyl (meth)acrylate, isomyristyl (meth)acrylate, and isostearyl (meth)acrylate. The branched alkyl group-containing monomer may be a branched alkyl (meth)acrylate monomer in which the alkyl group has a carbon number of C1 to C18. The branched alkyl group-containing monomer may have a branched structure in which the alkyl group has two or more branches (for example, two or more side chains to the main chain), such as a t-butyl group.

[0036] In the pressure-sensitive adhesive composition according to the present invention, the hydroxyl group-containing copolymerizable vinyl monomer may be at least one of hydroxyl group-containing alkyl (meth)acrylates such as 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, etc., and hydroxyl group-containing (meth)acrylamides such as N-hydroxy(meth)acrylamide, N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, etc. Among them, it is preferable that the hydroxyl group-containing copolymerizable vinyl monomer is at least one selected from the group consisting of 8-hydroxyoctyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate. The acrylic polymer according to the present invention contains 0.1 to 3.5 parts by weight of a hydroxyl-containing copolymerizable vinyl monomer per 100 parts by weight of the total of monomers (monomers belonging to the first monomer group) excluding the hydroxyl-containing copolymerizable vinyl monomer.

[0037] In the pressure-sensitive adhesive composition according to the present invention, the acrylic polymer preferably does not contain a (meth)acrylate monomer having an aromatic group from the viewpoint of lowering the dielectric constant of the pressure-sensitive adhesive layer. Similarly, the acrylic polymer may not contain a copolymerizable vinyl monomer having an aromatic group (such as styrene) as well as a (meth)acrylate having an aromatic group. In addition, the acrylic polymer preferably does not contain a copolymerizable vinyl monomer having a carboxyl group from the viewpoint of avoiding the influence on the corrosiveness of an adherend that is easily corroded, such as the ITO surface of a transparent conductive film. The acid value of the acrylic polymer is preferably 0.1 or less.

[0038] The polymerization method for the copolymer used as the acrylic polymer is not particularly limited, and any known polymerization method such as solution polymerization, emulsion polymerization, etc. The acrylic polymer preferably contains 50 to 100% by weight of an acrylic monomer such as a (meth)acrylate monomer.

[0039] The properties of the pressure-sensitive adhesive composition, such as required physical properties, can be adjusted by blending a crosslinking agent and / or any appropriate additives with the acrylic polymer.

[0040] Examples of the crosslinking agent include at least one polyisocyanate compound such as biuret modified or isocyanurate modified diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. The acrylic polymer preferably has a hydroxyl group as a functional group capable of crosslinking with the isocyanate compound of the crosslinking agent, and preferably contains a monomer having such a functional group in the side chain.

[0041] The content of the isocyanate compound used as the crosslinking agent is preferably 0.01 to 1.5 parts by weight per 100 parts by weight of the total of monomers (monomers belonging to the first monomer group) excluding the hydroxyl group-containing copolymerizable vinyl monomer. Only the isocyanate compound may be used as the crosslinking agent. As the isocyanate compound, an adduct of tolylene diisocyanate is preferred, and in particular, an adduct of tolylene diisocyanate and trimethylolpropane is preferred.

[0042] The pressure-sensitive adhesive composition preferably further contains a silane coupling agent. Examples of the silane coupling agent include compounds having at least one organic functional group and at least one hydrolyzable group in one molecule, the hydrolyzable group being an alkoxy group or the like bonded to a silicon atom. The silane coupling agent preferably has at least one organic functional group selected from the group consisting of an epoxy group, a (meth)acryloxy group, a mercapto group, and an amino group. Here, the (meth)acryloxy group means an acryloxy group (CH2=CHCOO-) or a methacryloxy group (CH2=C(CH3)COO-).

[0043] Examples of silane coupling agents having an epoxy group include 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 5,6-epoxyhexyltrimethoxysilane, 5,6-epoxyhexylmethyldimethoxysilane, 5,6-epoxyhexylmethyldiethoxysilane, and 5,6-epoxyhexyltriethoxysilane. Examples of silane coupling agents having a (meth)acryloxy group include 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, 3-(meth)acryloxypropyldimethylethoxysilane, and 3-(meth)acryloxypropyldimethylmethoxysilane. Examples of the silane coupling agent having a mercapto group include 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-mercaptopropylmethyldiethoxysilane, and 3-mercaptopropyltriethoxysilane. Examples of silane coupling agents having an amino group include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldiethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, 3-(methylamino)propyltrimethoxysilane, and 3-(methylamino)propyltriethoxysilane. Furthermore, alkoxy oligomers (silicone alkoxy oligomers) containing the above organic functional groups and oligomerized can also be used as silane coupling agents.

[0044] The content of the silane coupling agent is preferably 0.01 to 2.0 parts by weight per 100 parts by weight of the total of the monomers excluding the hydroxyl group-containing copolymerizable vinyl monomer (monomers belonging to the first monomer group).

[0045] Other optional components include known additives such as antioxidants, surfactants, hardening accelerators, plasticizers, fillers, crosslinking catalysts, crosslinking retarders, hardening retarders, processing aids, and antiaging agents. These may be used alone or in combination of two or more.

[0046] The pressure-sensitive adhesive layer of the present invention can be obtained by applying the pressure-sensitive adhesive composition to a substrate or a release film, and then crosslinking the pressure-sensitive adhesive composition. The gel fraction of the adhesive layer after crosslinking is preferably 40 to 75%. In addition, the weight-average molecular weight of the pressure-sensitive adhesive layer after crosslinking the pressure-sensitive adhesive composition is preferably 300,000 to 2,000,000. The weight-average molecular weight of the pressure-sensitive adhesive layer means the average value of all the components contained in the pressure-sensitive adhesive layer, but most of the weight of the pressure-sensitive adhesive layer is occupied by the acrylic polymer crosslinked with a crosslinking agent (crosslinked polymer) and the uncrosslinked acrylic polymer (uncrosslinked polymer). In this case, the weight-average molecular weight of the pressure-sensitive adhesive layer substantially corresponds to the weight-average molecular weight obtained by averaging the crosslinked polymer and the uncrosslinked polymer.

[0047] When used for bonding between layers of optical components, a thin adhesive layer is desirable. The thickness of the adhesive layer is preferably 1 μm to 25 μm, more preferably 5 μm to 25 μm. In general, the adhesive strength of an adhesive layer is approximately proportional to the thickness of the adhesive layer, and the adhesive strength of an adhesive layer having a thickness of 25 μm is preferably 1.5 to 10 N / 25 mm as the adhesive strength after 10 days at 23° C. The adherend used for the adhesive strength test includes glass plates such as alkali-free glass, resin films, and the like.

[0048] When the pressure-sensitive adhesive layer according to the present invention is used for bonding between layers of optical members, it is desirable that the difference in refractive index between the pressure-sensitive adhesive layer and the optical member is as small as possible in order to reduce the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical member. For this reason, the refractive index of the pressure-sensitive adhesive layer is preferably 1.47 to 1.50.

[0049] When the pressure-sensitive adhesive layer according to the present invention is used in an electronic device such as a touch panel, from the viewpoint of reducing electromagnetic field noise, it is preferable that the pressure-sensitive adhesive layer has a relative dielectric constant of 1.50 to 5.50 and a dielectric loss of 0.01 to 0.09 at a frequency of 100 kHz, measured after being laminated to a thickness of 1000 μm.

[0050] The pressure-sensitive adhesive film of the present invention can be produced by forming the pressure-sensitive adhesive layer of the present invention on one side of a substrate or a release film. As the base film used for forming the pressure-sensitive adhesive layer and the release film (separator) for protecting the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or the like, or an antistatic treatment by coating or kneading an antistatic agent, on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed.

[0051] The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. A "release film / adhesive layer / release film" configuration can be achieved by combining the release-treated surfaces of a release film on both sides of a single adhesive layer. In this case, the release films on both sides are peeled off sequentially or simultaneously to expose the adhesive surface, making it possible to attach it to an optical component such as an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films.

[0052] The adhesive film of the present invention can be used for bonding various optical films for peripheral components of liquid crystal display devices, mainly polarizing plates, various optical films for touch panels, various optical films for electronic paper, various optical films for organic electroluminescence (EL) displays, etc. In addition, the optical film may be an optical film with a pressure-sensitive adhesive layer, in which the pressure-sensitive adhesive layer is laminated on at least one surface of the optical film.Specific examples of the optical film include structures such as "optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / release film", "optical film / pressure-sensitive adhesive layer", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / optical film", "optical film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film", and "release film / pressure-sensitive adhesive layer / optical film / pressure-sensitive adhesive layer / release film". For example, in the case of "optical film / adhesive layer / release film" having an adhesive layer protected by a release film, the release film can be peeled off to expose the adhesive layer as in "optical film / adhesive layer", and then laminated with another optical film, thereby obtaining a configuration such as "optical film / adhesive layer / optical film" in which the adhesive layer is used for interlayer bonding.

[0053] The adhesive film of the present invention is preferably used for bonding a polarizing plate and a display panel. Examples of the display panel include a liquid crystal panel and an organic EL panel. The adhesive film of the present invention can be preferably used as an adhesive layer of a polarizing plate with an adhesive layer. A retardation film having a phase difference of λ / 4 or λ / 2 may be used as a constituent material of the polarizing plate. The adhesive layer of the present invention can be used for bonding a retardation film and a polarizing plate. According to the adhesive film of the present invention, since the adhesive layer has a low dielectric constant, it can be preferably used for bonding an optical member between a polarizing plate and a backlight unit in an on-cell type display device in which a touch sensor is provided between a color filter and a polarizing plate. EXAMPLES

[0054] The present invention will now be described in detail with reference to examples.

[0055] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 100 parts by weight of butyl acrylate, 0.2 parts by weight of 8-hydroxyoctyl acrylate, and 60 parts by weight of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65°C for 6 hours to obtain an acrylic polymer solution 1 used in Example 1. A portion of the acrylic polymer was collected and used as a sample for measuring the acid value described below. [Examples 2 to 4 and Comparative Examples 1 to 3] The acrylic polymer solutions used in Examples 2 to 4 and Comparative Examples 1 to 3 were obtained in the same manner as in the acrylic polymer solution 1 used in Example 1 above, except that the monomer compositions were as shown in Groups (1) and (2) in Table 1.

[0056] <Production of Pressure-Sensitive Adhesive Composition, Pressure-Sensitive Adhesive Layer, and Pressure-Sensitive Adhesive Film> [Example 1] To the acrylic polymer solution 1 of Example 1 produced as described above, 0.2 parts by weight of Coronate L (a 75% ethyl acetate solution of a trimethylolpropane (TMP) adduct of a tolylene diisocyanate (TDI) compound) and 0.05 parts by weight of KBM-403 (3-glycidoxypropyltrimethoxysilane) were added and stirred to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film (a silicone resin-coated polyethylene terephthalate (PET) film), dried at 90°C to remove the solvent, and then aged for 7 days under an atmosphere of 23°C and 50% RH to obtain an adhesive film of Example 1 having an adhesive layer of 25 μm in thickness formed by crosslinking the adhesive composition on one side of the release film. [Examples 2 to 4 and Comparative Examples 1 to 3] The pressure-sensitive adhesive films of Examples 2 to 4 and Comparative Examples 1 to 3 were obtained in the same manner as the pressure-sensitive adhesive film of Example 1 above, except that the compositions of the additives were as shown in Groups (3) and (4) of Table 1, respectively.

[0057] [Table 1]

[0058] In Table 1, the total of the monomer group (1) consisting of an alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer is taken as 100 parts by weight. The weight parts are shown in parentheses as the addition ratios of the monomers of groups (2) to (4). However, in Example 2, the total of group (1) was 90 parts by weight. In Comparative Examples 1 and 2, group (1) further contains a (meth)acrylate monomer having an aromatic group. The (2) group is a hydroxyl group-containing copolymerizable vinyl monomer, but in Comparative Examples 1 and 3, it is a monomer group consisting of a hydroxyl group-containing copolymerizable vinyl monomer and a carboxyl group-containing copolymerizable vinyl monomer. The (3) group is a crosslinking agent. The (4) group is a silane coupling agent.

[0059] The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Coronate (registered trademark) L is a product name of Nippon Polyurethane Industry Co., Ltd., D-110N is a product name of Mitsui Chemicals, Inc., and KBM-403 and KBM-803 are product names of Shin-Etsu Chemical Co., Ltd. TDI means tolylene diisocyanate, TMP means trimethylolpropane, and XDI means xylylene diisocyanate.

[0060] [Table 2]

[0061] <Test methods and evaluation> The release film (silicone resin-coated PET film) was peeled off from the pressure-sensitive adhesive film in Examples 1 to 4 and Comparative Examples 1 to 3 to expose the pressure-sensitive adhesive layer, which was then transferred to one side of a polarizing plate (film).

[0062] <Method of measuring adhesive strength> A 25 μm thick adhesive layer was transferred onto one side of a 180 μm thick polarizing plate (film) to obtain an adhesive film (optical film with an adhesive layer) as a sample. The obtained adhesive film was laminated with a pressure roller to the non-tin side of alkali-free glass that had been cleaned with acetone, and then autoclaved at 50°C, 0.5 MPa for 20 minutes, and then returned to an atmosphere of 23°C and 50% RH for 1 hour. The peel strength of the adhesive film was then measured using a tensile tester in accordance with JIS Z0237 "Test method for adhesive tapes and adhesive sheets," and the peel strength when peeled in a 180° direction at a speed of 300 mm / min was taken as the adhesive strength of the adhesive layer of the adhesive film (N / 25 mm).

[0063] <Acid value measurement method> The acid value of the acrylic polymer was measured by dissolving the sample in a solvent (a mixture of diethyl ether and ethanol in a volume ratio of 2:1) and titrating it with an automatic potentiometric titrator (Kyoto Electronics Manufacturing Co., Ltd., AT-610) using a 0.1 mol / l potassium hydroxide ethanol solution. The amount of potassium hydroxide ethanol solution required to neutralize the sample was measured. The acid value was then calculated using the following formula. Acid value = (B × f × 5.611) / S B = Amount (ml) of 0.1 mol / l potassium hydroxide ethanol solution used in titration f=factor of 0.1 mol / l potassium hydroxide ethanol solution S = mass of solids in the sample (g)

[0064] <Method of measuring gel fraction> After aging, the mass of the measurement sample before bonding to the polarizing plate was accurately measured, and it was immersed in toluene for 24 hours and then filtered through a 200-mesh wire screen. The filtered material was then dried at 100°C for 1 hour, and the mass of the residue was accurately measured to calculate the gel fraction of the adhesive layer (adhesive after crosslinking) using the following formula. Gel fraction (%) = insoluble portion mass (g) / adhesive mass (g) × 100

[0065] <Durability test method> A 10 cm square adhesive film prepared in the same manner as in measuring the adhesive strength was attached to the non-tin side of alkali-free glass in the same manner to create a sample.The sample was then left in a specified atmosphere (80°C dry atmosphere, or 60°C x 90% RH atmosphere) for 250 hours, then removed from the sample and placed in a 23°C x 50% RH atmosphere. After 1 hour, the condition of the adhesive film was visually observed to determine its durability. ○ The adhesive film does not peel off or foam at all. △: Peeling and bubbling have occurred in some parts of the adhesive film. × Peeling and bubbling have occurred over the entire adhesive film.

[0066] <Method of measuring dielectric constant and dielectric loss> A pressure-sensitive adhesive layer having a thickness of 1000 μm was used as a measurement sample. Using an LCR meter, the measurement sample was clamped between the fixtures of the LCR meter, and the relative dielectric constant and dielectric loss were measured at frequencies of 100 to 200 kHz.

[0067] <On-cell panel response> A polarizing plate with a 20 μm thick adhesive layer applied on one side was attached to an on-cell panel (TOD, Touch On Display), and then a touch operation was performed from the surface of the polarizing plate. The response reactivity was investigated when the touch operation was performed at different locations, and was evaluated according to the following criteria. ○ Good response responsiveness. × Poor response responsiveness.

[0068] <Reworkability test method> A 10 cm square adhesive film prepared in the same manner as in the adhesive strength measurement was attached to the non-tin side of alkali-free glass in the same manner to create a sample. The sample was left in an atmosphere of 70°C for 10 days, then removed to an atmosphere of 23°C and left for 1 hour, after which the adhesive strength of the adhesive film was measured to determine its reworkability. ○The adhesive strength after 10 days at 70℃ is 1.5~10N / 25mm. △ The adhesive strength after 10 days at 70℃ is greater than 10N / 25mm but less than 20N / 25mm. × The adhesive strength after 10 days at 70℃ is greater than 20N / 25mm (cannot be peeled off).

[0069] Tables 3 and 4 show the evaluation results.

[0070] [Table 3]

[0071] [Table 4]

[0072] The adhesive films of Examples 1 to 4, which are the adhesive films according to the present invention, have an adhesive strength of 1.5 to 10 N / 25 mm after 23°C x 10 days of an adhesive layer having a thickness of 25 μm, a gel fraction of the adhesive layer after crosslinking of 40 to 75%, a weight average molecular weight of the adhesive layer after crosslinking of 300,000 to 2,000,000, and an acid value of the acrylic polymer of 0.1 or less, and are excellent in adhesion and durability. In addition, the adhesive films of Examples 1 to 4 are excellent in reworkability because the adhesive strength after 70°C x 10 days is in the range of 1.5 to 10 N / 25 mm after being attached to an adherend. That is, the adhesive films of Examples 1 to 4 were able to overcome the requirements and problems in the prior art.

[0073] In the adhesive film of Comparative Example 1, the constituent monomer of the acrylic polymer did not contain butyl acrylate, but contained a (meth)acrylate monomer having an aromatic group and a copolymerizable vinyl monomer containing a carboxyl group, the gel fraction of the adhesive layer was low, the weight average molecular weight of the adhesive layer after crosslinking was small, and the acid value of the acrylic polymer was high. Perhaps due to these influences, when the thickness of the adhesive layer was 25 μm, the adhesive strength of the adhesive layer was strong, the durability at 80°C dry was slightly poor, the durability in an atmosphere of 60°C x 90% RH was poor, and the reworkability was slightly poor. In addition, the relative dielectric constant and dielectric loss were high, and the on-cell panel response was poor.

[0074] In the adhesive film of Comparative Example 2, the constituent monomer of the acrylic polymer contained a (meth)acrylate monomer having an aromatic group, the content of the hydroxyl group-containing copolymerizable vinyl monomer was high, the amount of the crosslinking agent added was large, and the gel fraction was high. Perhaps due to these influences, when the thickness of the adhesive layer was 25 μm, the adhesive strength of the adhesive layer was strong, the durability in an atmosphere of 60°C x 90% RH was poor, and the reworkability was somewhat poor. In addition, the dielectric loss was high, and the on-cell panel response was poor.

[0075] The adhesive film of Comparative Example 3 did not contain a crosslinking agent, so the acrylic polymer was not crosslinked, the gel fraction was 0, and the weight average molecular weight of the adhesive layer after crosslinking was small. In addition, the acrylic polymer contained a carboxyl group-containing copolymerizable vinyl monomer, and the acid value was high. Perhaps due to these influences, when the thickness of the adhesive layer was 25 μm, the adhesive strength of the adhesive layer was very strong, and the durability and reworkability were poor. In addition, the relative dielectric constant was high, and the on-cell panel response was poor.

[0076] As described above, the adhesive films of Comparative Examples 1 to 3 were unable to overcome the requirements and problems of the prior art. [Explanation of symbols]

[0077] 1...touch panel, 2...liquid crystal panel, 3...backlight unit, 4...space, 5...liquid crystal panel equipped with touch panel, 10...touch sensor, 11, 12...glass substrate, 13...color filter, 14, 15...polarizing plate, 16...transparent electrode, 17...TFT electrode, 18...liquid crystal layer, 20...liquid crystal panel, 30...backlight unit, 40...liquid crystal panel equipped with on-cell type touch panel.

Claims

1. a pressure-sensitive adhesive layer obtained by crosslinking a pressure-sensitive adhesive composition containing an acrylic polymer and a crosslinking agent, The acrylic polymer is (A) 100 parts by weight in total of at least one monomer selected from the group consisting of an alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer; (B) a copolymer obtained by copolymerizing 0.1 to 0.5 parts by weight of a hydroxyl group-containing copolymerizable vinyl monomer, (A) a total of 100 parts by weight of at least one monomer selected from a group consisting of an alkyl (meth)acrylate monomer having an alkyl group with a carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer contains 30 parts by weight or more of butyl (meth)acrylate, and at least two monomers selected from a group consisting of butyl (meth)acrylate, isobornyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; The acrylic polymer does not contain a (meth)acrylate monomer having an aromatic group and a carboxyl group-containing copolymerizable vinyl monomer, The acid value of the acrylic polymer is 0.1 or less, The pressure-sensitive adhesive layer is characterized by comprising, as the crosslinking agent, 0.01 to 1.5 parts by weight of an isocyanate compound that is an adduct of tolylene diisocyanate, relative to 100 parts by weight in total of at least one monomer group consisting of (A) an alkyl (meth)acrylate monomer having an alkyl group carbon number of C1 to C14, an alicyclic-containing monomer, and a branched-structure alkyl group-containing monomer.

2. 10. A pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer according to claim 1 laminated on one surface of a substrate.

3. 10. A pressure-sensitive adhesive film comprising the pressure-sensitive adhesive layer according to claim 1 formed on one side of a release film with a thickness of 1 μm to 25 μm, and having a structure of release film / pressure-sensitive adhesive layer / release film.

4. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and the pressure-sensitive adhesive layer according to claim 1 laminated on at least one surface of the optical film.

Citation Information

Patent Citations

  • Optical film and liquid crystal display device

    JP1998044291A

  • Pressure-sensitive adhesive composition for optical film, pressure-sensitive adhesive layer for optical film, production method thereof, pressure-sensitive adhesive optical film and image display

    JP2009120805A

  • Display device and method of driving the same

    JP2009258182A

  • Adhesive composition for optical member, adhesive type optical member and image display device

    JP2009258499A

  • Capacitive touch panel

    JP2012094017A